Pengembangan Aplikasi Android Bantuan Diri (Self Help) dalam Perencanaan Pendidikan Lanjutan Siswa Kelas IX MTs Negeri 8 Banyuwangi - Rizki Iswar Annas; Budi Purwoko; Tamsir Muis (Universitas Mathla'ul Anwar Banten, 2021)
ANDROID APPLICATION DEVELOPMENT OF SELF HELP IN PLANNING FOR FURTHER EDUCATION FOR CLASS IX STUDENTS OF MTS NEGERI 8 BANYUWANGI. This study aims to determine the development and feasibility of self-help android applications in the planning of advanced education for students of MTsN 8 banyuwangi. The use of the research and development method contains ten stages, namely, gathering information and research studies and issues in the field, planning, developing the initial product or media form, validating the initial product or media stages, revising the product or media, testing the product, operational improvement product, operational testing phase, product improvement stage or final media, distribution and reporting. The results of research have produced an android application of self-help in the planning of further education for students of MTsN 8 Banyuwangi with the feasibility according to the results of research by media experts obtaining Very Good quality with a score of 46 (92%), assessment from experts material obtains Very Good quality with a score of 46 (92%), the assessment of the teacher (small group) obtains Very Good quality with an average score of 64.67 and a percentage of 92.3%, the assessment of the teacher obtained very good quality with an average score of 64.4 and a percentage of 92.28%. When applied to students in small groups, the average score was 35.8 with a percentage of 89.5%. While the results of the assessment of students in large groups obtained an average value of 36.7 with a percentage of 91.75%.